PERSEPSI, CUSTOMER RELATIONSHIP MANAGEMENT DAN LOYALITAS - Septian Wahyudi (Universitas Riau, 2016)
Perception, Customer Relationship Management (CRM) and loyalty. The purpose of this study was conducted to determine the effect of customer perception and customer relationship management (CRM) .In this research methodology is descriptive and quantitative with SPSS, where the sample used in this study are customers of BRI Syariah. To determine the sample using the formula Slovin, sampling with accidental sampling method. Techniques of collecting data through observation and questionnaires. The data analysis was descriptive and multiple linear regression with SPSS version 19. From the results of data analysis and the perception that the contribution of CRM on customer loyalty with value F table (F count = 93.955> F table = 3.089) with the contribution of the coefficient of determination (R2) by 66% with the remaining 34%. Significant contribution in partial perception of the T table (3.710 count T> T table 1.985), while the variable partial CRM significance to the value table T (T 6.810 arithmetic> T table 1.985).